Evaluating facilitation and mentoring in a Management and Leadership Fundamentals programme (MLF) for registered nurses - Coetzee, Catherina Maria (Kayline) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.